Transformasi Dan Inovasi Perguruan Tinggi Islam Menjadi Universitas Kelas Dunia - Mochamad Chairudin; Lestari Widodo (DAARUS TSAQOFAH Jurnal Pendidikan Pascasarjana Universitas Qomaruddin, 2024)
Facing globalization and global competition, Islamic Religious Universities (PTKI) in Indonesia must continue innovating to achieve World Class University (WCU) status. This innovation effort covers several aspects, including improving academic quality, strengthening institutional capacity, and expanding general study programs. Additionally, it is anticipated that PTKI will play a pivotal role in promoting mutual understanding between the public and the Islamic community, serving as a hub for extensive Islamic studies, and actively participating in the Religious Moderation movement. To do this, PTKI must use creative approaches to education and study. This study employed a descriptive qualitative approach to library research. Books, scholarly publications, encyclopedias, and other relevant texts were among the many literary sources used to compile the data. To assess PTKI's progress towards WCU, the study offers a strategic review of the organization's role in national development. The history of PTKI's development in Indonesia, from its beginnings as an Islamic College (STI) to the establishment of the Indonesian Syekh Nurjati Cyber Islamic University (UISSI) in 2021, reflects the transformation carried out in response to the double disruption in 2020, namely technological innovation. PTKI must carry out its role as a responsive educational institution capable of producing quality graduates and contributing to community development. PTKI's development vision until 2045 involves strengthening internal capacity, expanding study programs, and contributing to national development.